Jock Young, left realism and critical victimology - Walklate, Sandra (Critical criminology, 2015)
In this paper I reflect upon the legacy of the work of Jock Young for the development of a critical criminology. In doing this I also endeavour to offer a contribution to an internal history of both criminology and victimology but from a very particular, and personal, position. The paper falls into four parts. In the first I consider the time period from 1980-1997 and academic, political and policy debates therein. I have called this a time of ‘emergent optimism’. The second part considers the years from 1997-2007 in which this optimism was subjected to challenge. The third part considers 2007 to date and the challenges that remain for both criminology and victimology in the absence of the voice of Jock Young.